Biological Sex, Estradiol and Striatal Medium Spiny Neuron Physiology: A Mini-Review - Krentzel, Amanda A.; Meitzen, John (Frontiers in Cellular Neuroscience, 2018)
The caudate-putamen, nucleus accumbens core and shell are important striatal brain regions for premotor, limbic, habit formation, reward, and other critical cognitive functions. Striatal-relevant behaviors such as anxiety, motor coordination, locomotion, and sensitivity to reward, all change with fluctuations of the menstrual cycle in humans and the estrous cycle in rodents. These fluctuations implicate sex steroid hormones, such as 17β-estradiol, as potent neuromodulatory signals for striatal neuron activity. The medium spiny neuron (MSN), the primary neuron subtype of the striatal regions, expresses membrane estrogen receptors and exhibits sex differences both in intrinsic and synaptic electrophysiological properties. In this mini-review, we first describe sex differences in the electrophysiological properties of the MSNs in prepubertal rats. We then discuss specific examples of how the human menstrual and rat estrous cycles induce differences in striatal-relevant behaviors and neural substrate, including how female rat MSN electrophysiology is influenced by the estrous cycle. We then conclude the mini-review by discussing avenues for future investigation, including possible roles of striatal-localized membrane estrogen receptors and estradiol.